The Ideal Use of Catheters in Hypospadias Repair: An Experimental Study - Polat, Haci; Gulacti, Umut (Urology Journal, 2016)
Purpose: To find answers to some catheter-related questions in hypospadias repair such as which type of catheter should be used, with which catheter balloon inflation volume, and when should the catheter be removed from the urethra? As catheter use and post-op retention time varies among surgeons in hypospadias repair. Material and methods: Fifty-four 10 French all-silicone- and 54 latex Foley catheters were prepared and assigned to groups as senary. The catheter’s balloons were inflated with 2, 3 and 5 mL of sterile water. The catheters were submerged in artificial human urine and then removed from the solution at 24, 72, and 168 h after submersion. The catheter balloon volume losses, increases in the transverse diameter of the catheters, and angulation of the catheter tips were measured to determine catheter degradation. Results: The minimum balloon volume loss was 0.4 mL in the group of all-silicone catheters that were inflated with 2mL and deflated after 24h (2mL 24h). According to balloon volume and deflation time, there were no increases in transverse diameter of the four groups of all-silicone catheters; 2mL 24h, 3mL 24h, 5mL 24h, and 2mL 72h. With 1 mm expansion, the lowest increase on transverse diameter of the latex catheters occurred in five groups; 2mL 24h, 3mL 24h, 5mL 24h, 2mL 72h, and 2mL 168h. Conclusion: An all-silicone catheter inflated with 2mL and removed from the urethra within 24-72 hours may be the ideal catheter use in hypospadias repair.